REDUCTION OF FLOOD DISCHARGE USING PERFORATED HORIZONTAL RECHARGE PIPES - Susilo, Edy; Budiningrum, Diah Setyati; Kustirini, Anik (Politeknik Negeri Semarang, 2023)
Despite implementing many recharge wells, the groundwater recharge with wells is still minimal. The hydrostatic pressure of the recharge well is only experienced at the bottom of the well which caused surface runoff. This study aims to formulate water recharge with Type T Perforated Horizontal Recharge Pipes (PHRP-T) to analyze the need for reducing surface runoff discharge. Water recharge with PHRP-T is greater than recharge wells. Using the experimental method, the recharge test was carried out with the independent variables of soil permeability (K), pipe wall porosity (P), pipe diameter (D), the length of the perforated horizontal pipe (L), and water pressure level (H). The recharge was observed from lowering the water level in the vertical pipe PHRP-T. A statistical program was performed to analyse the relationship between water absorption (Q) as the dependent variable with a regression equation. PHRP-T implementation to reduce surface runoff discharge can be applied to the hydrograph and rational methods. The findings of PHRP-T are significant for reducing flooding and increasing groundwater availability.